Interaction of the Klaipėda sea port and railway transport - Burkovskis, Raimondas; Palšaitis, Ramūnas (Transport, 2002)
This article offers the panoramic view to interoperability of sea and railway transport in Lithuania. Serious attention is being given to the cargo tlows forecasts, analysis of geographic, political, legal, economical, technical and other factors influencing the intensity of transit cargo flows and using the existing infrastructure capacities. Improvement and further development of technological and technical base of railways for the development of container transportation is identified. Optimization of tariffs (railway + port) will increase the competitiveness of corridor IX B for Iransit cargo and traffic flows. First Published Online: 19 Oct 2011